MIMETIC DESIRE IN CHRISTOPHER PRIEST THE PRESTIGE (LITERA KULTURA : Journal of Literary and Cultural Studies, 2017)
ABSTRACT The problem of desire is actually on how it uses an object to distract its purest condition; mimetic what the other desire. This “mimetic desire” situates the rivalry as it clearly appears in Christopher Priest’s The Prestige which narrates two characters (Angier and Borden) who want to succeed as magician by failing each other. Based on it, the formulated problems are; (1) how are Borden’s and Angier’s mimetic desire portrayed in Christopher Priest’ The Prestige? And (2) what are the impacts of their mimetic desire toward the conflicts between Borden and Angier in Christopher Priest’ The Prestige? To support the answer, the used theory is Girard’s Mimetic Desire. In the method, the approach is objective, the data collection is documentation (quoting), and the analysis is critical interpretation. It can be seen clearly that Borden wants to see Angier fails behind his desire to be success. On the other side, Angier wants to see Borden fails behind his desire to be success. In the beginning, Borden and Angier are magician, for Borden, Angier is the mediator to lead him to success, so is Angier. But, the situation changes, the mediator turns to be the obstacle for subject to reach the object and it makes the subject thinks that the mediator is the rivalry. Here, both Borden and Angier always blame each other and look for each failure. From those all, it concludes that Borden and Angier fail each other to be success although in the beginning, they appreciate each other. It means that desire changes from imitating to rivalry Keyword: Mimetic, Desire, rivalry, Angier, and Borden. ABSTRACT Masalah pada hasrat sebenarnya adalah bagaimana menggunakan objek untuk menganggu kondisi termurni subjek, meniru apa yang orang lain hasrati. Hasrat meniru ini menempatkan persaingan yang terlihat jelas muncul dalam novel The Prestige karya Christopher Priest yang mana dalam novel ini menceritakan dua karakter (Angier and Borden) yang ingin sukses menjadi seorang pesulap dengan menjatuhkan satu sama lain. Berdasarkan hal tersebut , rumusan masalahnya adalah; (1) Bagaimana Hasrat meniru Borden dan Angier digambarkan dalam novel The Prestige karya Christipher Priest? (2). Apa dampak hasrat meniru mereka terhadap konflik antara Borden dan Angier dalam novel The Prestige karya Christopher Priest? Untuk mendukung jawaban dari rumusan masalah tersebut, teori yang digunakan adalah Teori Hasrat Meniru Girard. Dalam motode penelitannya mengunakan pendekatan objektif, pengumpulan data dengan dokumentasi (mengutip) dan analisis dengan interpretasi kritis. Hal ini bisa terlihat jelas bahwa Borden ingin melihat Angier gagal di balik hasratnya ntuk menjadi sukses. Pada mulanya, Borden dan Angier adalah pesulap, bagi Borden, Angier adalah mediator untuk menuntunnya meraih kesuksesan, begitu juga Angier. Tetapi situasi berubah, mediator berubah menjadi penghambat bagi subjek untuk mendapatkan objek dan hal tersebut membuat subjek berfikir bahwa mediator adalah persaingan. Disini, Borden dan Angier selalu menyalahkan satu sama lain dan mencari kegagala masing-masing. Dari semua hal itu, dapat disimpulkan bahwa Borden dan Angier menjatuhkan satu sama lain untuk menjadi sukses, meskipun pada awalnya , mereka mengharga satu sama lain. Hal ini berarti hasrat berubah dari meniru menjadi rivalitas. Kata kunci: Mimesis, Hasrat, Rivalitas, Angier, and Borden.